Traditional Chinese medicine promotes the control and treatment of dementia - Tao, Pengyu; Xu, Wenxin; Gu, Simeng; Shi, Haiyan; Wang, Qian; Xu, Yuzhen (Frontiers in Pharmacology, 2022)
Dementia is a syndrome that impairs learning and memory. To date, effective therapy has not solved dementia. Current prescription drugs, such as cholinesterase inhibitors, fail to improve the condition of dementia, which is often accompanied by severe adverse effects. In recent years, studies on the use of traditional Chinese medicine (TCM) for dementia treatment has increased, revealing that the formula could significantly improve memory and cognitive dysfunctions in animal models. TCM showed fewer adverse effects, lower cost, and suitability for long-term use. Due to ingredient complexity and bioactivity variety of herb medicine, the multi-target nature of the traditional Chinese formula affected the outcome of dementia therapy. Innovation in TCM will create a new platform for new drug development for the prevention and treatment of dementia, further strengthening and enhancing the current influence of TCM.